Pre-service Teachers' Readiness For Digital Technology ‎integration: The Case Of Ecole Normal Supérieure El Katiba ‎assia Djebbar Constantine - Touatit, Belkais; Mezhoud, Soraya (The Journal of Studies in Language, Culture, and Society, 2025)
In today's digital educational landscape, effectively preparing pre-service teachers to integrate ‎technology into their teaching practices is essential. This study investigated the preparedness of ‎‎146 final-year pre-service teachers at the Teacher Training School of Constantine, Algeria, for ‎integrating digital technologies into their pedagogical practices. Utilizing an explanatory ‎sequential mixed-methods design, data were collected via a survey assessing pre-service ‎teachers' self-reported digital literacy levels and knowledge of technology integration ‎frameworks, achieving a 69% response rate (N=101). Subsequently, semi-structured interviews ‎were conducted with a purposive sample of 8 student teachers to explore the quantitative ‎findings in greater depth. While pre-service teachers demonstrated high self-reported digital ‎literacy and positive attitudes towards technology integration, interview results revealed a ‎discrepancy between their perceived abilities and their practical application of technology in ‎teaching. These findings highlight the need for teacher education programs to emphasize ‎practical training in technology integration and to equip teacher educators with the skills and ‎knowledge necessary to effectively model digital technology integration for pre-service teachers. ‎Moreover, the study suggests that improving access to technological resources and providing ‎targeted training on utilizing diverse technological tools are crucial steps in preparing pre-service ‎teachers for the demands of 21st-century education.‎